THE EFFECT OF FIBER VOLUME FRACTION IN OIL PALM EMPTY FRUIT BUNCH COMPOSITES ON TENSILE AND IMPACT PROPERTIES - Sirajuddin, Awal Syahrani (Jurnal Sains dan Teknologi Tadulako, 2026)
This study aims to analyse the effect of the fiber weight fraction of oil palm empty bunch fiber (OPEBF) composite with HDPE matix on tensile strength and impact. The composite fabrication process is performed using the hot compression method for 210oC with a weight fraction of 40, 50, and 60% fiber. The results showed that the highest tensile strength of the composite fraction of 40% fiber was 3.461 MPa and its modulus of elasticity was 97.702 MPa, followed by the fraction of 50% fiber with a value of 2.948 MPa, the modulus of elasticity was 88.544 MPa, and the lowest value was in the fraction of 60% fiber with a value of 2.205 MPa, and the modulus of elasticity was 87.622 MPa. Furthermore, the highest effort in the impact test on the weight fraction of 40% fiber is 4,249 Joules and an impact energy value of 8364,744 Joules/mm2, followed by a weight fraction of 50% fiber with an effort value to break the specimen of 3,935 Joules and an impact energy value of 7745,651 Joules/mm2, and the lowest attempt to break the specimen at the weight fraction of 60% fiber has a value of 3,341 Joules and has an impact energy of 6576,934 Joules/mm2.